PENDAMPINGAN MANAJEMEN PENGELOLAAN TAMBAK UDANG - Agung Praptapa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Munggangsari is one of the villages in the Purworejo Regency area, which is located on the coast, and has great potential in the fisheries (catch and cultivation) and marine sector. In the areas near the beach, they are mostly used for shrimp farming. The shrimps are usually managed by locals or professional, but the investors are mostly from area out of this regency. Unfortunately, people who work in the shrimp are good in growing shrimp, but they are still have some lacks in term of management. For this reason, coaching the shrimp farmers are important to do, to help them make good performance in term of shrimp productivity and sustainable business. The coaching includes the aspects of human resources, financial, production, and marketing. The method of coaching is through discussion and presentation of the case. This is not just a one-day coaching, but continuous coaching to help farmers do sustainable business which is expected by investors.